Tanzanian Women Exposed to Nutrition-Related Media Messages and Interpersonal Counselling Are More Likely Than Unexposed Women to Practice Optimal Nutrition Behaviors. (7th June 2021) - Callaway, Sarah; Mulokozi, Generose; Crookston, Benjamin T.; Fulbright, Emma; Donoso, Paola; Quintana, Noyra Melissa; Hall, P. Cougar; Linehan, Mary; Torres, Scott; West, Josh; Dearden, Kirk
Abstract: Objectives: We tested the hypothesis that mothers of infants < 2 y of age who were exposed to nutrition- and health-focused radio and TV spots, interpersonal counselling (IPC), or both were more likely than mothers with no exposure to media nor to IPC to practice the following behaviors during their most recent pregnancy: eat more food than usual, eat more frequently than usual, eat more types of food than usual, make at least one antenatal care (ANC) visit, receive or purchase iron tablets, and reduce household workload. Methods: Between 2016 and 2020, the Addressing Stunting in Tanzania Early (ASTUTE) project conducted a social and behavior change intervention in the Lake zone of Tanzania that reached 8.4 million individuals, including 4.4 million people through radio and TV spots, 6.4 million through community health worker home visits, 411, 000 through support groups, and 1.6 million through health facility-based counselling. We administered a cross-sectional survey to 5, 000 households with children < 2 y before the intervention and 5, 000 households after program activities ended. We used bivariate analyses and logistic regression to test our hypotheses. Results: After adjusting for maternal age, education, and household wealth, IPC alone was only associated receiving ANC (OR: 1.7, p = 0.008). Exposure to media alone was significantly associated with every behavior except self-reported increased food consumption (OR range for all comparisons: 1.2–1.9; p < 0.001). Exposure to both media and IPC was associated with every behavior (p < 0.001 for all comparisons) and the odds of practicing such behaviors were greater than for media alone (OR range: 1.6–3.8; p < 0.01 for all comparisons). Conclusions: In this program setting, exposure to IPC alone was not associated with nutrition and health behaviors in pregnancy but media and media + IPC were strongly associated with such practices. Media and IPC have the potential to improve maternal nutrition, an often-neglected public health challenge. Funding Sources: ASTUTE was funded by UKAid (contract # PO 6803).